Wear-resistant PVC floor film and preparation method thereof
Patent Information
- Application Number
- CN202611375541.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]针对现有技术的不足,本发明提供了一种耐磨PVC地板膜及其制备方法,具备耐磨性能优异、力学强度高、环保性能好以及尺寸稳定性佳的优点,解决了现有技术中耐磨性与力学性能难以兼顾、增塑剂迁移导致VOCs排放高、压延工艺粘辊及膜厚不均导致尺寸稳定性差的问题
[0050]1、本发明通过采用低PVC用量与热塑性聚氨酯弹性体共混形成海岛结构耐磨分散相,并配合乙烯-醋酸乙烯酯-马来酸酐三元共聚物(EVA-g-MAH)增容剂的化学键合作用改善两相界面结合,同时引入改性蒙脱土与KH-570表面改性纳米二氧化硅实现层状与球形双重纳米增强,辅以交联剂构建三维网络结构,从材料配方层面实现耐磨性能的协同提升,解决了现有技术中耐磨性与力学性能难以兼顾的技术难题。
Smart Images

Figure CN122978614A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PVC flooring membrane technology, specifically to a wear-resistant PVC flooring membrane and its preparation method. Background Technology
[0002] PVC flooring membrane, as an important floor decoration material, has advantages such as slip resistance, wear resistance, easy cleaning, and convenient installation. It is widely used in public places such as shopping malls, airports, hospitals, schools, stadiums, vehicles, and ships, as well as in home decoration. With the rapid development of modern industry, construction, and home decoration, the market's performance requirements for PVC flooring membrane are increasing.
[0003] Currently, commercially available wear-resistant PVC flooring films are mainly produced using a high amount of PVC resin (usually 50-100 parts) as the matrix material, combined with plasticizers, heat stabilizers, and inorganic wear-resistant fillers, processed through mixing, plasticizing, calendering, and other processes. However, existing technologies still have many shortcomings in terms of raw material formulation and preparation processes:
[0004] Firstly, regarding abrasion resistance, traditional PVC floor membranes primarily rely on the PVC resin matrix itself and the addition of micron- or nano-sized inorganic fillers (such as alumina and silica) to improve abrasion resistance. However, the abrasion resistance of PVC material itself is limited, making it difficult to meet long-term usage requirements in high-traffic areas. Furthermore, inorganic abrasion-resistant fillers generally suffer from uneven dispersion and agglomeration when blended with the PVC matrix, which not only weakens the reinforcing effect of the fillers but also leads to inconsistent abrasion resistance in different parts of the membrane. In addition, the excessive amount of PVC resin used in existing technologies limits the flexibility and impact resistance of the membrane, making it difficult to achieve a good balance between abrasion resistance and mechanical properties.
[0005] Secondly, regarding environmental performance, existing technologies mostly use traditional plasticizers such as dioctyl terephthalate (DOP). These plasticizers are prone to migration and volatilization during use, which not only leads to a gradual decrease in the flexibility of the film layer but also releases large amounts of volatile organic compounds (VOCs) and semi-volatile organic compounds (SVOCs), causing indoor air pollution and adverse effects on human health. Meanwhile, some existing technologies use heat stabilizers containing heavy metals such as lead and cadmium, posing serious environmental pollution and health hazards during their production and use. Although there has been a trend in recent years to replace DOP with dioctyl terephthalate (DOTP) and heavy metal stabilizers with calcium-zinc composite stabilizers, the heat stabilization efficiency of existing environmentally friendly additive systems remains low, and problems such as precipitation, discoloration, and decreased mechanical properties easily occur during processing.
[0006] Secondly, regarding the manufacturing process, existing calendering technologies mostly employ vertical four-roll calendering or horizontal five-roll calendering schemes. During the material exiting the die and entering the calendering roll assembly, the lack of intermediate support rollers causes the material to sag naturally due to gravity, necessitating increased roll speed to straighten it, resulting in increased shrinkage of the finished product. Simultaneously, the small contact area between the substrate and the roll assembly during calendering leads to rapid and uneven temperature loss, further exacerbated by the traction effect of the exiting plate, ultimately resulting in increased longitudinal shrinkage and warping of the finished product. Furthermore, traditional calendering processes suffer from coarse roll temperature control, lacking gradient temperature control design, resulting in significant film thickness unevenness. High-temperature processing also easily leads to substantial volatilization of plasticizers and thermal degradation of PVC. Roll sticking during calendering has long plagued manufacturers, severely impacting production efficiency and product quality.
[0007] In summary, existing wear-resistant PVC floor membranes have significant shortcomings in terms of wear resistance, environmental performance, and manufacturing process. There is an urgent need for a new type of wear-resistant PVC floor membrane and its manufacturing method that can simultaneously improve wear resistance, mechanical properties, and environmental performance while optimizing the manufacturing process. Summary of the Invention
[0008] (a) Technical problems to be solved
[0009] To address the shortcomings of existing technologies, this invention provides a wear-resistant PVC flooring film and its preparation method, which has the advantages of excellent wear resistance, high mechanical strength, good environmental performance, and good dimensional stability. It solves the problems in existing technologies, such as the difficulty in achieving both wear resistance and mechanical properties, high VOC emissions due to plasticizer migration, and poor dimensional stability caused by roller sticking during calendering and uneven film thickness.
[0010] (II) Technical Solution
[0011] To achieve the above objectives, the present invention provides the following technical solution: a wear-resistant PVC flooring membrane, wherein the raw materials and their weight parts of the flooring membrane are: 38-43 parts of PVC blended resin; 12-15 parts of thermoplastic polyurethane elastomer; 2-3.5 parts of ethylene-vinyl acetate-maleic anhydride terpolymer; 1-2 parts of modified montmorillonite; 1.3-2 parts of modified nano-SiO2; 1.3-2.6 parts of ultra-high molecular weight polyethylene wax; 6.5-9.7 parts of dioctyl terephthalate; 2-3.2 parts of epoxidized soybean oil; 1.6-2.6 parts of organotin-zinc composite stabilizer; 0.3-0.65 parts of oxidized polyethylene wax; 0.2-0.32 parts of stearic acid; 0-3.2 parts of rutile titanium dioxide; 0.3-0.52 parts of hindered amine light stabilizer; 0.2-0.52 parts of titanate coupling agent; and antioxidant 245. 0.065-0.2 parts; dispersant 0.2-0.39 parts; flame retardant and smoke suppressant 1.3-2 parts; crosslinking agent 0.13-0.32 parts.
[0012] Preferably, the modification process of the modified montmorillonite is as follows:
[0013] S1.1 Pretreatment: Sodium montmorillonite is vacuum dried at 70-80℃ for 3-4 hours;
[0014] S1.2 Ion exchange: Disperse montmorillonite in deionized water at a mass ratio of 1:5, add hexadecyltrimethylammonium bromide at 28%-30% of the mass of montmorillonite, and react for 3-4 hours at 75-80℃ and 300-400 rpm.
[0015] S1.3 Washing and centrifugation: Wash with a 1:1 volume ratio of ethanol-water mixture until no Br⁻ is detected, and then separate at 7000-8000 rpm for 10-15 min.
[0016] S1.4 Spray drying: The obtained separated product is spray dried at an inlet temperature of 180-200℃ and an outlet temperature of 90-100℃. The feed concentration is set at 15%-20%, the feed rate is 50-100mL / min, and the atomizing disc speed is 25000-30000rpm. After spray drying, the product is further dried in a vacuum drying oven at 80-85℃ for 2-3 hours until constant weight.
[0017] S1.5 Post-pulverization treatment: Finally, the modified montmorillonite is pulverized by an air jet mill until the particle size is ≤5μm and passed through a 2500-mesh sieve.
[0018] Preferably, the modification process of the modified nano-SiO2 is as follows:
[0019] S2.1 Dispersion and activation: Dry nano-SiO2 with a particle size of 15±5nm in an oven at 105-110℃ for 1.5-2.5h, put it into a high-speed mixer, and add 70%-80% ethanol solution at a mass ratio of 1:10 while stirring at 800-1000rpm.
[0020] S2.2 Coupling reaction: Add 1.8%-2% of the silane coupling agent KH-570 (by mass of SiO2) to a constant pressure dropping funnel at a dropping rate of 1-3 mL / min. After the addition is complete, adjust the pH to 4.5-5.5 with acetic acid (5%-10% by mass). React in a constant temperature water bath at 58-60℃ with a stirring speed of 600-1000 rpm for 1.8-2 hours.
[0021] S2.3 Desolventizing and Dispersing: After the reaction is completed, the product is distilled under reduced pressure for 1-2 hours at 55-65℃ and a vacuum degree of -0.08 to -0.095 MPa to obtain the modified nano-SiO2 product for later use.
[0022] Preferably, the flame retardant and smoke suppressant is selected from one or a combination of two of zinc molybdate, zinc borate, and antimony trioxide; the crosslinking agent is selected from one of trimethylolpropane trimethacrylate and triallyl isocyanurate; and the dispersant is selected from zinc stearate and polyethylene glycol monostearate.
[0023] A method for preparing a wear-resistant PVC floor membrane, comprising the following steps, based on the raw materials and their weight proportions described above:
[0024] Step 1: Raw material preparation: Prepare the following components by weight: PVC blended resin, thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano-SiO2, ultra-high molecular weight polyethylene wax, dioctyl terephthalate, epoxidized soybean oil, organotin-zinc composite stabilizer, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, titanate coupling agent, antioxidant 245, dispersant, flame retardant and smoke suppressant, and crosslinking agent.
[0025] Step 2, Raw material pretreatment: The PVC blended resin and thermoplastic polyurethane elastomer are dried and pretreated. Dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax are preheated before use.
[0026] Step 3, Mixing and Plasticizing: The dried PVC blended resin, dried thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano silica, ultra-high molecular weight polyethylene wax, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, antioxidant 245, dispersant and flame retardant smoke suppressant are sequentially added to a high-shear mixer. Then, preheated dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax are added sequentially to fully wet and adsorb onto the powder surface. Finally, organotin-zinc composite stabilizer, titanate coupling agent and crosslinking agent are added, and the mixture is stirred to obtain a plasticized mixture.
[0027] Step 4, Internal mixing and open milling: The plasticized mixture is fed into a pressure internal mixer for high-temperature and high-pressure melting and mixing, and then further plasticized by a two-roll open mill to obtain a uniformly plasticized sheet melt.
[0028] Step 5, Filtration and Extrusion: The sheet-like melt is fed into a single-screw filter extruder, where impurities are removed by filtration through a filter screen to obtain pure molten material;
[0029] Step 6, Five-roll calendering: The pure molten material is fed into a five-roll calender for gradient temperature-controlled calendering to obtain a preliminary PVC flooring film;
[0030] Step 7, Cooling and Winding: The initially formed PVC flooring film is sequentially subjected to embossing, gradient cooling, edge trimming, online thickness measurement feedback, and constant tension winding to finally obtain a wear-resistant PVC flooring film.
[0031] Preferably, the raw material pretreatment in step two includes:
[0032] (1) Place the PVC blended resin in an oven at 80-90℃ and dry for 2-3 hours until the moisture content is ≤0.02%; dry the thermoplastic polyurethane elastomer in a vacuum environment at a pressure ≤-0.09MPa and a temperature of 80-90℃ for 2-3 hours until the moisture content is ≤0.02%;
[0033] (2) Mix dioctyl phthalate and epoxidized soybean oil according to the formula ratio, then heat to 60-70℃ and keep warm, stirring at low speed of 95-100rpm for 20-30 minutes; preheat ultra-high molecular weight polyethylene wax separately to 80℃ to melt for later use.
[0034] Preferably, in step three, the mixture is plasticized:
[0035] S3.1. The dried PVC blended resin, dried thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano silica, ultra-high molecular weight polyethylene wax, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, antioxidant 245, dispersant and flame retardant smoke suppressant are sequentially added into a high shear mixer and stirred at 800-900 rpm for 10-15 min at 95-100℃.
[0036] S3.2 Add preheated dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax, and continue stirring at 600-700 rpm for 8-12 minutes.
[0037] S3.3 Finally, add the organotin-zinc composite stabilizer, titanate coupling agent and crosslinking agent, and stir at 500-600 rpm for 3-5 minutes to obtain a uniformly mixed plasticized mixture.
[0038] Preferably, the refining and initial refining processes in step four are as follows:
[0039] S4.1. Feed the plasticized mixture obtained in step three into a pressure mixer, set the mixing temperature to 155-165℃, the mixing time to 8-12min, and the rotor speed to 40-50rpm.
[0040] S4.2. After the material is discharged from the internal mixer, it is immediately transferred to a two-roll mill for open milling. The front roll temperature is set to 160-170℃, the rear roll temperature to 155-165℃, the roll gap to 1-3mm, the open milling time to 5-8min, and the material is passed through a thin mill 3-5 times to finally obtain a uniformly plasticized sheet melt.
[0041] Preferably, the filtration and extrusion conditions in step five are set as follows: the sheet-like melt obtained in step four is fed into a single-screw filter extruder, the screw length-to-diameter ratio is set to 20:1-25:1, the compression ratio is set to 2.5:1-3.0:1, the screw speed is controlled to 15-25 rpm, and the temperatures of each section of the extruder are set as follows: feeding section 155-160℃, compression section 165-170℃, homogenization section 170-175℃, and die head 175-180℃; a 120-200 mesh filter screen combination is set at the end of the extruder, and finally pure molten material is obtained.
[0042] Preferably, the five-roll calendering and preliminary shaping process in step six is as follows: the pure molten material obtained in step five is fed into a five-roll calender for calendering. The temperature gradient of the five rolls from bottom to top is set as follows: roll #1 167±1℃, roll #2 172±1℃, roll #3 177±1℃, roll #4 172±1℃, and roll #5 162±1℃. The roll speed ratio is controlled at 1:1.05-1:1.15. The film thickness is controlled at 0.20-0.50mm by adjusting the gap between each roll, and finally a preliminary PVC floor film is obtained.
[0043] In step seven, the post-processing and winding process involves sequentially treating the pre-formed PVC flooring sheet obtained in step six as follows:
[0044] (1) Embossing treatment: The surface is embossed by embossing rollers at a temperature of 55±0.5℃ and a linear speed of 25-35m / min;
[0045] (2) Gradient cooling and shaping: The product is subjected to gradient cooling and shaping through three sets of cooling rollers. The temperatures of the three sets of cooling rollers are set to 65±0.5℃, 45±0.5℃ and 25±0.5℃ respectively.
[0046] (3) Edge trimming: The edges are trimmed using an edge trimming device;
[0047] (4) Online thickness measurement feedback: The film thickness is monitored in real time by an online thickness detector and fed back to the calender to automatically adjust the roll gap, ensuring that the thickness deviation is ≤ ±0.005mm;
[0048] (5) Constant tension winding: The constant tension winding device is used to wind the film, and the winding tension is controlled at 2-5 N / cm² to obtain the wear-resistant PVC floor film.
[0049] Compared with the prior art, the present invention provides a wear-resistant PVC floor membrane and its preparation method, which has the following beneficial effects:
[0050] 1. This invention uses a low amount of PVC to blend with thermoplastic polyurethane elastomer to form a sea-island structure wear-resistant dispersed phase, and improves the interfacial bonding of the two phases by using ethylene-vinyl acetate-maleic anhydride terpolymer (EVA-g-MAH) compatibilizer. At the same time, modified montmorillonite and KH-570 surface-modified nano silica are introduced to achieve layered and spherical dual nano-reinforcement. A crosslinking agent is used to construct a three-dimensional network structure. This invention achieves a synergistic improvement in wear resistance from the material formulation level, and solves the technical problem of difficulty in achieving both wear resistance and mechanical properties in the prior art.
[0051] 2. This invention replaces traditional phthalic acid plasticizers with an environmentally friendly plasticizing system composed of dioctyl terephthalate and epoxidized soybean oil, and replaces heavy metal stabilizers with an organotin-zinc composite stabilizer. Combined with low-temperature mixing process and closed-loop filtration extrusion process, it effectively reduces plasticizer volatilization and VOC emissions from both the source of raw materials and the processing process, thereby reducing TVOC emissions from flooring films.
[0052] 3. This invention employs a five-roll gradient temperature-controlled calendering process combined with low-temperature extraction, and uses three sets of gradient cooling rollers for step-by-step cooling and shaping. It is further supplemented by an online thickness measurement closed-loop feedback system to adjust the film thickness in real time, thereby achieving precise thickness shaping and controllable stress release of the film material. This solves the problems of calendering roller sticking, uneven film thickness, warping deformation, and poor dimensional stability in the prior art. Attached Figure Description
[0053] Figure 1 This is a flowchart illustrating the preparation process of the floor membrane of this invention. Detailed Implementation
[0054] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0055] Please see Figure 1 A wear-resistant PVC flooring membrane, the raw materials and their functions are shown in the table below:
[0056] Table 1
[0057]
[0058]
[0059] A method for preparing a wear-resistant PVC floor membrane, comprising the following specific steps, based on the raw materials and their weight proportions described above:
[0060] Step 1: Raw material preparation: Prepare the following components by weight: PVC blended resin, thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano-SiO2, ultra-high molecular weight polyethylene wax, dioctyl terephthalate, epoxidized soybean oil, organotin-zinc composite stabilizer, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, titanate coupling agent, antioxidant 245, dispersant, flame retardant and smoke suppressant, and crosslinking agent.
[0061] Step 2: Raw material pretreatment is as follows:
[0062] (1) Place the PVC blended resin in an oven at 80-90℃ and dry for 2-3 hours until the moisture content is ≤0.02%; dry the thermoplastic polyurethane elastomer in a vacuum environment at a pressure ≤-0.09MPa and a temperature of 80-90℃ for 2-3 hours until the moisture content is ≤0.02%. This step can prevent moisture from vaporizing during high-temperature processing to generate bubbles and silver streaks, and at the same time avoid the decrease in molecular weight of PVC resin due to hydrolysis and the hydrolytic degradation of ester groups / urethane groups in TPU, ensuring that the internal structure of the film layer is dense, the surface is smooth and without defects, and guaranteeing mechanical properties and appearance quality.
[0063] (2) Mix dioctyl phthalate and epoxidized soybean oil according to the formula ratio, then heat to 60-70℃ and keep warm. Stir at low speed of 95-100rpm for 20-30 minutes to fully integrate the two and reduce the viscosity of the system. Preheat the ultra-high molecular weight polyethylene wax to 80℃ separately to melt it for later use. Preheating reduces the viscosity of the plasticizer system, making it easier for the PVC resin to absorb in the subsequent mixing and plasticizing steps, shortening the plasticizing time and improving the plasticizing uniformity. After the ultra-high molecular weight polyethylene wax is preheated and melted, it is added in liquid form to avoid the local lubrication failure caused by uneven dispersion of solid wax in the mixed system, ensuring that the synergistic effect of internal and external lubrication is fully exerted, thereby effectively eliminating the phenomenon of calender sticking to the roller and improving the smoothness of the film surface.
[0064] Step 3: Mixing and plasticizing:
[0065] S3.1. The dried PVC blended resin, dried thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano silica, ultra-high molecular weight polyethylene wax, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, antioxidant 245, dispersant and flame retardant smoke suppressant are sequentially added into a high shear mixer and stirred at 800-900 rpm for 10-15 minutes at 95-100℃ to ensure that all powder components are fully and evenly mixed.
[0066] S3.2 Add dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax that have been preheated at 50-60℃, and continue to stir at 600-700 rpm for 8-12 minutes to allow the liquid components to fully wet and adsorb onto the powder surface.
[0067] S3.3 Finally, add the organotin-zinc composite stabilizer, titanate coupling agent and crosslinking agent, and stir at 500-600 rpm for 3-5 minutes to obtain a uniformly mixed plasticized mixture.
[0068] Through the above steps, the raw material components are uniformly dispersed and fully plasticized in the resin matrix, so that the nano-reinforcing effect of modified montmorillonite and modified nano silica can be fully exerted, while avoiding the problems of plasticizer volatilization and thermal degradation caused by high-temperature processing in traditional processes.
[0069] Step four, the refining and initial refining process is as follows:
[0070] S4.1. Feed the plasticized mixture obtained in step three into a pressure mixer, set the mixing temperature to 155-165℃, the mixing time to 8-12min, and the rotor speed to 40-50rpm.
[0071] S4.2. After the material is discharged from the internal mixer, it is immediately transferred to a two-roll mill for open milling. The front roll temperature is set to 160-170℃, the rear roll temperature to 155-165℃, the roll gap to 1-3mm, the open milling time to 5-8min, and the material is passed through a thin mill 3-5 times to further plasticize the material evenly and remove volatile gases, so as to obtain a uniformly plasticized sheet melt.
[0072] By completing the above steps at a temperature of 155-165℃, the materials are fully plasticized and uniformly mixed, which can effectively avoid the risk of thermal degradation of thermoplastic polyurethane elastomer and ethylene-vinyl acetate-maleic anhydride terpolymer at high temperatures, while reducing the volatilization loss of plasticizers and lowering VOC emissions.
[0073] Step 5: Set the filtration and extrusion conditions as follows: Feed the sheet-like melt obtained in Step 4 into a single-screw filter extruder, set the screw length-to-diameter ratio to 20:1-25:1, the compression ratio to 2.5:1-3.0:1, control the screw speed to 15-25 rpm, and set the temperatures of each section of the extruder as follows: feeding section 155-160℃, compression section 165-170℃, homogenization section 170-175℃, and die head 175-180℃; install a 120-200 mesh filter combination at the end of the extruder to filter out unmelted particles, gel particles, and impurities to obtain pure molten material.
[0074] Through the above steps, unmelted particles, gel particles and impurities in the melt are removed by filtration, thereby ensuring the purity and surface quality of the film layer, and ultimately providing a uniform molten material for subsequent calendering, fundamentally eliminating the source of film surface defects.
[0075] Step Six, Five-Roll Calendering and Preliminary Shaping Process: The pure molten material obtained in Step Five is fed into a five-roll calender for calendering. The temperature gradient of the five rolls from bottom to top is set as follows: Roll 1# 167±1℃, Roll 2# 172±1℃, Roll 3# 177±1℃, Roll 4# 172±1℃, Roll 5# 162±1℃. The roll speed ratio is controlled at 1:1.05-1:1.15. The film thickness is controlled at 0.20-0.50mm by adjusting the gap between each roll, resulting in a pre-formed PVC floor film with uniform thickness and a smooth surface.
[0076] Step 7, Post-processing and winding: The pre-formed PVC flooring film obtained in Step 6 is processed as follows:
[0077] (1) Embossing treatment: The surface is embossed by embossing rollers at a temperature of 55±0.5℃ and a linear speed of 25-35m / min;
[0078] (2) Gradient cooling and shaping: The product is subjected to gradient cooling and shaping through three sets of cooling rollers. The temperatures of the three sets of cooling rollers are set to 65±0.5℃, 45±0.5℃ and 25±0.5℃ respectively.
[0079] (3) Edge trimming: The edges are trimmed using an edge trimming device;
[0080] (4) Online thickness measurement feedback: The film thickness is monitored in real time by an online thickness detector and fed back to the calender to automatically adjust the roll gap, ensuring that the thickness deviation is ≤ ±0.005mm;
[0081] (5) Constant tension winding: The constant tension winding device is used to wind the film, and the winding tension is controlled at 2-5 N / cm² to obtain the wear-resistant PVC floor film.
[0082] Through the above steps, a five-roll gradient temperature-controlled calendering process (165-180℃) combined with low-temperature extraction (162±1℃) is used to achieve precise thickness forming of the film material, which can effectively avoid the problem of roller sticking in the traditional high-temperature calendering process, while ensuring the uniformity of film thickness.
[0083] Example 1
[0084] A wear-resistant PVC flooring membrane, comprising the following raw materials and their weight proportions: 38 parts PVC blended resin (K value 72-75); 12 parts thermoplastic polyurethane elastomer; 2 parts ethylene-vinyl acetate-maleic anhydride terpolymer (EVA-g-MAH); 1 part modified montmorillonite; 1.3 parts modified nano-silica; 1.3 parts ultra-high molecular weight polyethylene wax (molecular weight 5000-10000); and 6 parts dioctyl terephthalate (DOTP). 0.5 parts; 2 parts epoxidized soybean oil (ESO); 1.6 parts organotin-zinc composite stabilizer; 0.3 parts oxidized polyethylene wax (OPE wax); 0.2 parts stearic acid; 0.3 parts hindered amine light stabilizer; 0.2 parts titanate coupling agent; 0.065 parts antioxidant 245; 0.2 parts dispersant; 1.3 parts flame retardant and smoke suppressant (zinc molybdate and zinc borate in a 1:1 mass ratio); 0.13 parts crosslinking agent (trimethylolpropane trimethacrylate).
[0085] This embodiment uses a transparent film without the addition of rutile titanium dioxide.
[0086] Example 2
[0087] A wear-resistant PVC flooring membrane, comprising the following raw materials and their weight parts: 40 parts PVC blended resin (K value 72-75); 13.5 parts thermoplastic polyurethane elastomer; 2.8 parts ethylene-vinyl acetate-maleic anhydride terpolymer (EVA-g-MAH); 1.5 parts modified montmorillonite; 1.7 parts modified nano-silica; 2 parts ultra-high molecular weight polyethylene wax (molecular weight 5000-10000); 8 parts dioctyl terephthalate (DOTP); 2.6 parts epoxidized soybean oil (ESO); 2 parts organotin-zinc composite stabilizer; 0.5 parts oxidized polyethylene wax (OPE wax); 0.26 parts stearic acid; 2 parts rutile titanium dioxide (R-996); 0.4 parts hindered amine light stabilizer; 0.35 parts titanate coupling agent; and 245 parts antioxidant. 0.13 parts; dispersant (zinc stearate) 0.3 parts; flame retardant and smoke suppressant (zinc borate and antimony trioxide in a 1:1 mass ratio) 1.7 parts; crosslinking agent (triallyl isocyanurate) 0.2 parts.
[0088] Example 3
[0089] A wear-resistant PVC flooring membrane, comprising the following raw materials and their weight parts: 43 parts PVC blended resin (K value 72-75); 15 parts thermoplastic polyurethane elastomer; 3.5 parts ethylene-vinyl acetate-maleic anhydride terpolymer (EVA-g-MAH); 2 parts modified montmorillonite; 2 parts modified nano-silica; 2.6 parts ultra-high molecular weight polyethylene wax (molecular weight 5000-10000); 9.7 parts dioctyl terephthalate (DOTP); 3.2 parts epoxidized soybean oil (ESO); 2.6 parts organotin-zinc composite stabilizer; 0.65 parts oxidized polyethylene wax (OPE wax); 0.32 parts stearic acid; 3.2 parts rutile titanium dioxide (R-996); 0.52 parts hindered amine light stabilizer; 0.52 parts titanate coupling agent; and 245 parts antioxidant. 0.2 parts; dispersant (polyethylene glycol monostearate) 0.39 parts; flame retardant and smoke suppressant (a mixture of zinc molybdate, zinc borate and antimony trioxide in a mass ratio of 1:1:1) 2 parts; crosslinking agent (trimethylolpropane trimethacrylate) 0.32 parts.
[0090] Comparative Example
[0091] Comparative Example 1 (Commercially available ordinary PVC flooring film, P-grade abrasion resistant)
[0092] A commercially available ordinary PVC flooring film comprises the following raw materials and parts by weight: 100 parts PVC resin (SG-5 type, K value 68-70); 25 parts dioctyl phthalate (DOP); 8 parts triisopropylphenyl phosphate; 5 parts calcium-zinc / barium-zinc composite stabilizer; 4 parts aluminum hydroxide (micron-sized); 2 parts magnesium hydroxide (micron-sized); 3 parts epoxidized soybean oil; 0.5 parts polyethylene wax; 0.5 parts stearic acid; and 5 parts rutile titanium dioxide (R-996). This formula uses traditional DOP plasticizer and calcium-zinc / barium-zinc composite stabilizer, with micron-sized aluminum hydroxide and magnesium hydroxide as flame-retardant fillers. No elastomer modifying components, nano-reinforcing materials, or crosslinking agents are added. Its abrasion resistance mainly depends on the PVC resin matrix itself, classifying it as a basic P-grade abrasion-resistant product available commercially.
[0093] Comparative Example 2 (Commercially available T-grade abrasion-resistant PVC flooring film)
[0094] A commercially available T-grade wear-resistant PVC flooring membrane comprises the following raw materials and parts by weight: 100 parts PVC resin (SG-5 type, K value 68-70); 28 parts dioctyl terephthalate (DOTP); 8 parts epoxidized soybean oil; 4 parts calcium-zinc composite stabilizer; 10 parts nano-alumina; 3 parts talc (1250 mesh); 0.5 parts stearic acid; 0.5 parts oxidized polyethylene wax; 8 parts rutile titanium dioxide (R-996); 0.2 parts antioxidant 1010; and 0.2 parts antioxidant 168. This formulation uses DOTP environmentally friendly plasticizer instead of DOP and nano-alumina (30-50nm) as a wear-resistant filler, achieving a wear resistance grade of T (Fv≤2.0). However, the nano-alumina is not surface-treated and easily agglomerates in the PVC matrix. Furthermore, the lack of compatibilizers and crosslinking agents in the formulation limits further improvements in mechanical properties and wear resistance.
[0095] Comparative Example 3 (Commercially available high-end homogeneous wear-resistant PVC flooring)
[0096] A commercially available high-end homogeneous wear-resistant PVC flooring comprises the following raw materials and their weight parts: 85 parts PVC resin (SG-5 type, K value 68-70); 15 parts chlorinated polyethylene (CPE); 20 parts dioctyl terephthalate (DOTP); 10 parts epoxidized soybean oil; 2.5 parts organotin stabilizer; 6 parts nano-silica (untreated); 5 parts nano-alumina (untreated); 0.5 parts stearic acid; 0.5 parts polyethylene wax; 5 parts rutile titanium dioxide (R-996); 0.2 parts antioxidant 1076; and 0.2 parts antioxidant 168. This formulation introduces CPE to toughen and modify PVC, and is compounded with dual inorganic nanofillers of nano-silica and nano-alumina, resulting in mechanical properties superior to Comparative Example 1 and Comparative Example 2. However, the inorganic fillers have not undergone surface modification treatment, resulting in insufficient dispersion and interfacial bonding strength in the PVC matrix. Furthermore, there are no dedicated compatibilizers to improve the CPE / PVC interfacial bonding and no crosslinking agents to form a three-dimensional network structure, leaving room for improvement in overall performance.
[0097] The wear-resistant PVC floor membranes prepared in Examples 1-3 of this invention were compared with commercially available products in Comparative Examples 1-3 in terms of wear resistance, mechanical properties, dimensional stability, and environmental performance. The test results are shown in Table 2.
[0098] Table 2
[0099]
[0100] Table 2 shows that the wear-resistant PVC floor membranes prepared in Examples 1-3 of this invention are significantly superior to those in Comparative Examples 1-3 in terms of wear resistance, mechanical properties, dimensional stability, and environmental performance. Specific comparisons are as follows:
[0101] (1) Wear resistance: The wear resistance grades of Examples 1-3 all reached Grade T and the Fv value ≤ 1.2 mm³ / 100 rpm. Among them, Example 3 was the best (Fv ≤ 0.9 mm³ / 100 rpm) and Taber wear amount ≤ 35 mg / 1000 rpm. However, Comparative Example 1 was only Grade P (Fv ≤ 8.0 mm³ / 100 rpm, Taber ≤ 80 mg). Although Comparative Examples 2 and 3 were Grade T, their Fv values were only ≤ 2.0 mm³ / 100 rpm and ≤ 1.8 mm³ / 100 rpm, and their Taber wear amounts were ≤ 50 mg and ≤ 45 mg, respectively. The wear resistance of the embodiments of the present invention is significantly better than that of commercially available Grade T products. This is due to the wear-resistant dispersed phase formed by the low PVC content in the raw materials and the TPU blend, as well as the synergistic effect of the dual nano-reinforcement of modified montmorillonite and modified nano-silica.
[0102] (2) Mechanical properties: The tensile strength (longitudinal) of Examples 1-3 is ≥15.0 MPa and the elongation at break (longitudinal) is ≥220%, and the tensile strength increases with the increase of TPU, modified montmorillonite and modified nano silica. Example 3 is the best (tensile strength ≥16.5 MPa, elongation at break ≥240%). The tensile strength of Comparative Examples 1-3 is only ≥10.0 MPa, ≥12.0 MPa and ≥13.5 MPa, and the elongation at break is only ≥160%, ≥180% and ≥200%, respectively. The tensile strength of the present invention is more than 22% higher than that of Comparative Example 3, and the elongation at break is more than 20% higher than that of Comparative Example 3. This is attributed to the chemical bonding effect of EVA-g-MAH compatibilizer on the TPU / PVC two-phase interface in the raw materials, and the enhancing effect of the three-dimensional network structure formed by the crosslinking agent on the film strength.
[0103] (3) Dimensional stability: The residual indentation of Examples 1-3 was ≤0.05mm, and the dimensional change rate after heat aging was ≤0.08%; while the residual indentation of Comparative Examples 1-3 was ≤0.10mm, ≤0.07mm and ≤0.06mm, and the dimensional change rate after heat aging was ≤0.20%, ≤0.13% and ≤0.10%, respectively. The residual indentation of the embodiments of the present invention was reduced by more than 17% compared with Comparative Example 3, and the dimensional change rate after heat aging was reduced by 40% compared with Comparative Example 3. This is because the nano-intercalation structure of the modified montmorillonite in the raw materials endows the film with excellent barrier properties and improved dimensional stability, and the moderate cross-linking network formed by the cross-linking agent endows the film with better creep resistance and heat shrinkage resistance.
[0104] (4) Environmental performance: The TVOC emissions of Examples 1-3 were all ≤3.0mg / m³, and showed a decreasing trend with the increase of DOTP and ESO dosage and the optimization of processing temperature, with Example 3 being the best (≤2.5mg / m³); while Comparative Example 1, which used DOP plasticizer, had TVOC emissions as high as 15.0mg / m³, and Comparative Examples 2 and 3 were ≤5.0mg / m³ and ≤4.5mg / m³, respectively. The TVOC emissions of the embodiments of the present invention are reduced by more than 44% compared with Comparative Example 3. This is because the present invention uses low-volatility environmentally friendly plasticizer DOTP and bio-based ESO, and combines a low-temperature mixing process of 155-165℃, effectively reducing the volatilization loss of plasticizer from both the source and process dimensions.
[0105] In summary, this invention provides a wear-resistant foundation through low PVC content and TPU blending modification, improves interfacial bonding through EVA-g-MAH compatibilizer, achieves dual nano-reinforcement through "modified montmorillonite + KH-570 modified nano-SiO2", forms a three-dimensional network structure through crosslinking agent, and achieves precise molding through five-roll gradient temperature-controlled calendering process with optimized parameters. The synergistic effect of each component makes the overall performance of Examples 1-3 significantly better than the three comparative examples. Among them, Example 3 is the optimal implementation scheme, achieving the best levels in wear resistance (Fv≤0.9mm³ / 100 rpm, Taber≤30mg), mechanical strength (tensile strength≥16.5MPa, elongation at break≥240%), dimensional stability (residual indentation≤0.04mm, thermal aging dimensional change rate≤0.06%), and environmental protection (TVOCs≤2.5mg / m³). It is suitable for high-traffic commercial venues, medical institutions, educational spaces, and public buildings with high environmental performance requirements.
[0106] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant PVC floor membrane, characterized in that, The raw materials and their weight parts of the floor membrane are as follows: 38-43 parts of PVC blended resin; 12-15 parts of thermoplastic polyurethane elastomer; 2-3.5 parts of ethylene-vinyl acetate-maleic anhydride terpolymer; 1-2 parts of modified montmorillonite; 1.3-2 parts of modified nano-SiO2; 1.3-2.6 parts of ultra-high molecular weight polyethylene wax; 6.5-9.7 parts of dioctyl terephthalate; 2-3.2 parts of epoxidized soybean oil; 1.6-2.6 parts of organotin-zinc composite stabilizer; 0.3-0.65 parts of oxidized polyethylene wax; 0.2-0.32 parts of stearic acid; and 0-3.2 parts of rutile titanium dioxide. Hindered amine light stabilizer 0.3-0.52 parts; titanate coupling agent 0.2-0.52 parts; antioxidant 245 0.065-0.2 parts; dispersant 0.2-0.39 parts; flame retardant and smoke suppressant 1.3-2 parts; crosslinking agent 0.13-0.32 parts.
2. The wear-resistant PVC floor membrane according to claim 1, characterized in that, The modification process of the modified montmorillonite is as follows: S1.1 Pretreatment: Sodium montmorillonite is vacuum dried at 70-80℃ for 3-4 hours; S1.2 Ion exchange: Disperse montmorillonite in deionized water at a mass ratio of 1:5, add hexadecyltrimethylammonium bromide at 28%-30% of the mass of montmorillonite, and react for 3-4 hours at 75-80℃ and 300-400 rpm. S1.3 Washing and centrifugation: Wash with a 1:1 volume ratio of ethanol-water mixture until no Br⁻ is detected, and then separate at 7000-8000 rpm for 10-15 min. S1.4 Spray drying: The obtained separated product is spray dried at an inlet temperature of 180-200℃ and an outlet temperature of 90-100℃. The feed concentration is set at 15%-20%, the feed rate is 50-100mL / min, and the atomizing disc speed is 25000-30000rpm. After spray drying, the product is further dried in a vacuum drying oven at 80-85℃ for 2-3 hours until constant weight. S1.5 Post-pulverization treatment: Finally, the modified montmorillonite is pulverized by an air jet mill until the particle size is ≤5μm and passed through a 2500-mesh sieve.
3. The wear-resistant PVC floor membrane according to claim 1, characterized in that, The modification process of the modified nano-SiO2 is as follows: S2.1 Dispersion and activation: Dry nano-SiO2 with a particle size of 15±5nm in an oven at 105-110℃ for 1.5-2.5h, put it into a high-speed mixer, and add 70%-80% ethanol solution at a mass ratio of 1:10 while stirring at 800-1000rpm. S2.2 Coupling reaction: Add 1.8%-2% of the silane coupling agent KH-570 (by mass of SiO2) to a constant pressure dropping funnel at a dropping rate of 1-3 mL / min. After the addition is complete, adjust the pH to 4.5-5.5 with acetic acid (5%-10% by mass). React in a constant temperature water bath at 58-60℃ with a stirring speed of 600-1000 rpm for 1.8-2 hours. S2.3 Desolventizing and Dispersing: After the reaction is completed, the product is distilled under reduced pressure for 1-2 hours at 55-65℃ and a vacuum degree of -0.08 to -0.095 MPa to obtain the modified nano-SiO2 product for later use.
4. The wear-resistant PVC floor membrane according to claim 1, characterized in that, The flame retardant and smoke suppressant is selected from one or a combination of two of zinc molybdate, zinc borate, and antimony trioxide; the crosslinking agent is selected from one of trimethylolpropane trimethacrylate and triallyl isocyanurate; and the dispersant is selected from zinc stearate and polyethylene glycol monostearate.
5. A method for preparing a wear-resistant PVC floor membrane, characterized in that, The preparation of a wear-resistant PVC floor membrane according to claim 1, using raw materials and their weight proportions, includes the following steps: Step 1: Raw material preparation: Prepare the following components by weight: PVC blended resin, thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano-SiO2, ultra-high molecular weight polyethylene wax, dioctyl terephthalate, epoxidized soybean oil, organotin-zinc composite stabilizer, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, titanate coupling agent, antioxidant 245, dispersant, flame retardant and smoke suppressant, and crosslinking agent. Step 2, Raw material pretreatment: The PVC blended resin and thermoplastic polyurethane elastomer are dried and pretreated. Dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax are preheated before use. Step 3, Mixing and Plasticizing: The dried PVC blended resin, dried thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano silica, ultra-high molecular weight polyethylene wax, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, antioxidant 245, dispersant and flame retardant smoke suppressant are sequentially added to a high-shear mixer. Then, preheated dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax are added sequentially to fully wet and adsorb onto the powder surface. Finally, organotin-zinc composite stabilizer, titanate coupling agent and crosslinking agent are added, and the mixture is stirred to obtain a plasticized mixture. Step 4, Internal mixing and open milling: The plasticized mixture is fed into a pressure internal mixer for high-temperature and high-pressure melting and mixing, and then further plasticized by a two-roll open mill to obtain a uniformly plasticized sheet melt. Step 5, Filtration and Extrusion: The sheet-like melt is fed into a single-screw filter extruder, where impurities are removed by filtration through a filter screen to obtain pure molten material; Step 6, Five-roll calendering: The pure molten material is fed into a five-roll calender for gradient temperature-controlled calendering to obtain a preliminary PVC flooring film; Step 7, Cooling and Winding: The initially formed PVC flooring film is sequentially subjected to embossing, gradient cooling, edge trimming, online thickness measurement feedback, and constant tension winding to finally obtain a wear-resistant PVC flooring film.
6. The method for preparing a wear-resistant PVC floor membrane according to claim 5, characterized in that, The raw material pretreatment in step two: (1) Place the PVC blended resin in an oven at 80-90℃ and dry for 2-3 hours until the moisture content is ≤0.02%; dry the thermoplastic polyurethane elastomer in a vacuum environment at a pressure ≤-0.09MPa and a temperature of 80-90℃ for 2-3 hours until the moisture content is ≤0.02%; (2) Mix dioctyl phthalate and epoxidized soybean oil according to the formula ratio, then heat to 60-70℃ and keep warm, stirring at low speed of 95-100rpm for 20-30 minutes; preheat ultra-high molecular weight polyethylene wax separately to 80℃ to melt for later use.
7. The method for preparing a wear-resistant PVC floor membrane according to claim 5, characterized in that, The mixing and plasticizing process in step three: S3.
1. The dried PVC blended resin, dried thermoplastic polyurethane elastomer, ethylene-vinyl acetate-maleic anhydride terpolymer, modified montmorillonite, modified nano silica, ultra-high molecular weight polyethylene wax, oxidized polyethylene wax, stearic acid, rutile titanium dioxide, hindered amine light stabilizer, antioxidant 245, dispersant and flame retardant smoke suppressant are sequentially added into a high shear mixer and stirred at 800-900 rpm for 10-15 min at 95-100℃. S3.2 Add preheated dioctyl terephthalate, epoxidized soybean oil and ultra-high molecular weight polyethylene wax, and continue stirring at 600-700 rpm for 8-12 minutes. S3.3 Finally, add the organotin-zinc composite stabilizer, titanate coupling agent and crosslinking agent, and stir at 500-600 rpm for 3-5 minutes to obtain a uniformly mixed plasticized mixture.
8. The method for preparing a wear-resistant PVC floor membrane according to claim 5, characterized in that, The refining and initial refining processes in step four are as follows: S4.
1. Feed the plasticized mixture obtained in step three into a pressure mixer, set the mixing temperature to 155-165℃, the mixing time to 8-12min, and the rotor speed to 40-50rpm. S4.
2. After the material is discharged from the internal mixer, it is immediately transferred to a two-roll mill for open milling. The front roll temperature is set to 160-170℃, the rear roll temperature to 155-165℃, the roll gap to 1-3mm, the open milling time to 5-8min, and the material is passed through a thin mill 3-5 times to finally obtain a uniformly plasticized sheet melt.
9. The method for preparing a wear-resistant PVC floor membrane according to claim 5, characterized in that, In step five, the filtration and extrusion conditions are set as follows: the sheet-like melt obtained in step four is fed into a single-screw filter extruder, the screw length-to-diameter ratio is set to 20:1-25:1, the compression ratio is set to 2.5:1-3.0:1, the screw speed is controlled to 15-25 rpm, and the temperatures of each section of the extruder are set as follows: feeding section 155-160℃, compression section 165-170℃, homogenization section 170-175℃, and die head 175-180℃; a 120-200 mesh filter screen is installed at the end of the extruder, and finally, pure molten material is obtained.
10. The method for preparing a wear-resistant PVC floor membrane according to claim 5, characterized in that, The five-roll calendering and preliminary shaping process in step six is as follows: The pure molten material obtained in step five is fed into a five-roll calender for calendering. The temperature gradient of the five rolls from bottom to top is set as follows: Roll 1# 167±1℃, Roll 2# 172±1℃, Roll 3# 177±1℃, Roll 4# 172±1℃, Roll 5# 162±1℃. The roll speed ratio is controlled at 1:1.05-1:1.
15. The film thickness is controlled at 0.20-0.50mm by adjusting the gap between each roll. Finally, a preliminary PVC floor film is obtained. In step seven, the post-processing and winding process involves sequentially treating the pre-formed PVC flooring sheet obtained in step six as follows: (1) Embossing treatment: The surface is embossed by embossing rollers at a temperature of 55±0.5℃ and a linear speed of 25-35m / min; (2) Gradient cooling and shaping: The product is subjected to gradient cooling and shaping through three sets of cooling rollers. The temperatures of the three sets of cooling rollers are set to 65±0.5℃, 45±0.5℃ and 25±0.5℃ respectively. (3) Edge trimming: The edges are trimmed using an edge trimming device; (4) Online thickness measurement feedback: The film thickness is monitored in real time by an online thickness detector and fed back to the calender to automatically adjust the roll gap, ensuring that the thickness deviation is ≤ ±0.005mm; (5) Constant tension winding: The constant tension winding device is used to wind the film, and the winding tension is controlled at 2-5 N / cm² to obtain the wear-resistant PVC floor film.